Contribution of healthy and unhealthy primary school meals to greenhouse gas emissions in England: linking nutritional data and greenhouse gas emission data of diets - Wickramasinghe, Kremlin Khamarj (Eur J Clin Nutr, 2016)
BACKGROUND/OBJECTIVE: School meals represent the largest sector in Government food procurement in the UK. This paper aims to quantify, simultaneously, the nutritional quality and carbon footprint of meals provided by primary schools in England. METHODS: The School Food Trust conducted the “Primary School Food Survey 2009” (PSFS) in a nationally representative sample of 139 primary schools in England. The survey included 6,690 students who consumed school lunches and 3,488 students who brought packed lunches. We estimated the total greenhouse gas emissions (GHGEs) per Kg of the food items contributing to those lunches based on the results of a systematic review of life cycle analyses. RESULTS: In both school lunches and packed lunches the “meat, fish and alternatives” group contributed the largest share of GHGEs. The mean GHGE value per school lunch was estimated to be 0.72 (95% uncertainty interval 0.52-1.34) KgCO(2)e and per packed lunch as 0.70 (0.58-0.94) KgCO2e. The total GHGEs due to primary school meals in England per year is 578.1 million KgCO2e (455 million-892 million). CONCLUSION: If all children achieved a healthy meal defined by having a low level of salt, free sugars and saturated fat the total GHGEs from primary school meals would be 441.2 million KgCO2e (384 – 1,192), saving 136.9million KgCO2e compared to the current total emissions from primary school meals. This paper demonstrates that changes in the primary school food sector can have an impact on UK greenhouse gas emissions.